Pro SQL Server on Microsoft Azure - Mazumdar, Pranab; Agarwal, Sourabh; Banerjee, Amit (Apress : Imprint: Apress, 2016)
Learn the basics of Microsoft Azure and see how SQL Server on Azure VMs (Infrastructure-as-a-Service) and Azure SQL Databases (Platform-as-a-Service) work. This concise book shows you how to deploy, operate, and maintain your data using any one or a combination of these offerings along with your on-premise environment. Pro SQL Server on Microsoft Azure is a quintessential book for any IT professional who is planning to host their data on Microsoft Azure. This book will not only equip you with the tips, tricks, and tools to manage SQL Server offerings on Azure, but will also help you in deciding between PaaS, IaaS, or hybrid. In the ever-changing world of operations, IT administrators and SQL Server DBAs often find that the biggest challenges occur once they've deployed to the cloud. This is precisely why Pro SQL Server on Microsoft Azure was written. It will help you master today's cloud world, focusing on the following issues: Understanding the Microsoft Azure IaaS architecture Working with Azure Storage and Networking Deploying SQL Server on Azure VMs using best practices Applying effective security principles to SQL Azure Databases Measuring and optimizing the performance of SQL Server offerings on Azure Implementing Business continuity and disaster recovery options with Azure SQL Databases .